2018
DOI: 10.1007/jhep08(2018)018
|View full text |Cite
|
Sign up to set email alerts
|

Twisted Hilbert spaces of 3d supersymmetric gauge theories

Abstract: We study aspects of 3d N = 2 supersymmetric gauge theories on the product of a line and a Riemann surface. Performing a topological twist along the Riemann surface leads to an effective supersymmetric quantum mechanics on the line. We propose a construction of the space of supersymmetric ground states as a graded vector space in terms of a certain cohomology of generalized vortex moduli spaces on the Riemann surface. This exhibits a rich dependence on deformation parameters compatible with the topological twis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 64 publications
0
48
0
Order By: Relevance
“…Let us first consider the cohomology of the two complexes on the left hand side. The maps α 0 and α 1 are injective and surjective respectively and therefore the cohomology can be written as 13) which corresponds to the tangent space of the symmetric product at the point D. It follows that some of the massless fermionic fluctuations at the point D encoded by the complexes span the tangent space to the bosonic moduli space, as expected [42]. By Serre duality, it is then easy to see that the combination of the two complexes on the right of (5.12) define the contangent space T * M m over the moduli space.…”
Section: Sqed[1]mentioning
confidence: 64%
See 2 more Smart Citations
“…Let us first consider the cohomology of the two complexes on the left hand side. The maps α 0 and α 1 are injective and surjective respectively and therefore the cohomology can be written as 13) which corresponds to the tangent space of the symmetric product at the point D. It follows that some of the massless fermionic fluctuations at the point D encoded by the complexes span the tangent space to the bosonic moduli space, as expected [42]. By Serre duality, it is then easy to see that the combination of the two complexes on the right of (5.12) define the contangent space T * M m over the moduli space.…”
Section: Sqed[1]mentioning
confidence: 64%
“…A second interesting extension would be to introduce background vector bundles for the flavour symmetries G H and G C on Σ. This is relatively straightforward for G H , but in the case of G C these are expected to induce vector bundles on the moduli spaces of solutions themselves [42], and it would be of great mathematical appeal to uncover generalisations of this phenomenon. It is also possible to study the inclusion of line operators wrapping S 1 , which are similar to the above.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Protected indices in supersymmetric QFT often have an interpretation in terms of the geometry of an appropriate moduli space of classical solutions. In recent work, Bullimore et al [5,6], have suggested such an interpretation for the twisted index. In this paper we will confirm this proposal and extend it in several ways.…”
Section: Jhep08(2020)015mentioning
confidence: 92%
“…Using modern terminology, one might call H(F g ) a categorification of the A-model. A chiral multiplet of R-charge R contributes to this Q A -cohomology a boson φ and a fermion ψ, which after the twist transform as holomorphic sections of K [82,91,93,94]:…”
Section: Jhep09(2020)152mentioning
confidence: 99%